Pengaruh Jus Buah Apel Merah (Pyrus malus L.) Terhadap Kadar Kolesterol HDL (High Density Lipoprotein) Darah Tikus Putih Jantan Galur Wistar (Rattus norvegicus) - Nelwan, Gabriel N; Wullur, Adeanne C; Bodhi, Widdhi (UNIVERSITAS SAM RATULANGI, 2012)
The aims of this research were to study the effect of red apple juice (Pyrus malus L.)on Blood HDL cholesterol (High Density Lipoprotein) of white male mice strain wistar(Rattus norvegicus).This research using experimental method,and Pre and Post testRandomized Controlled Group Design. The subjects in these research were 25 mices, whichpossess 180-200g weight. Mices were divided into 5 groups, namely negative control(aquadest), positive control (Simvastatin) and Pyrus malus juice treatments concentration 2ml per day treatment (P1), 4 ml/day treatment (P2) and 8 ml/day treatment (P3). Every groupconsists of five mices.Treatment starts by feds mices with high content of lipids diet for tendays.At day eleven, all mices were analyzedits HDL cholesterol (pre-test).Thenall miceswere feds with high content of lipids diet and its treatment.After ten days of treatment, posttestwere conducted.Data were analyzed using spss ver.19. The differences betweentreatmentswere analyzed usingone way ANOVA. The results shows that 8 ml/day Pyrusmalus juice significantly increase HDL cholesterol of white male wistar(p<0,05). Pyrusmalus juice(P3)possess activity as simvastatin.Keywords: Pyrus malus L., Rattus norvegicus L., HDL cholesterol